Pengaruh Waktu Tunggu, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Maskapai Garuda Indonesia Di Terminal 3 Bandara Soekarno Hatta - Bunga Ayu Lestari (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study to determine the effect of waiting time, price and quality of service to customer satisfaction and analyze the most dominant variable affecting consumer satisfaction. Based on the results of this study is expected to realize the management of companies more effective and efficient. Population in this research is all passengers who use flight service from Garuda Indonesia Airlines terminal 3 at the Soekarno Hatta Airport Tangerang. Sampling technique conducted by the writer is Purpose Sampling, so that in the study only taken 100 passengers that using Garuda Indonesia Airlines. Method of data collection using questionnaire method and data analysis test method using quantitative analysis with hypothesis proof. Hypothesis testing conducted is classical assumption test, multiple linear regression analysis, coefficient of determination (R2), “t” test ND “F” test. Based on the result of data analysis and hypothesis testing, it can be concluded as follows : 1)Waiting time partially influential and significant to customer satisfaction, 2) price partially influential and significant to customer satisfaction, 3) quality of service partially significant and significant customer satisfaction, 4) waiting time, price and service quality simultaneously have an effecr on and significant to customer satisfaction.